Respuesta :
The inverse function : [tex]f^{-1}(x)=\sqrt{x-5}[/tex]
Further explanation
A ƒunction can be expressed in the form of a cartesian diagram, sequential pairs, or arrow diagrams
If a ƒunction (f) pairs members of set A to set B, then the inverse of ƒunction f (f⁻¹) pairs members of set B to A, or easily f⁻¹ is the opposite of f
or in the form of equations :
f (x) = y if and only if g (y) = x
g (y) is called the inverse of f (x)
The step for determining the inverse ƒunction
1. expresses the ƒunction y = f (x) in the form x = f (y)
2. f⁻¹(y) = g(y)
3. Replace the letter y with x so we get the inverse ƒunction formula f⁻¹(x)
Known :
f (x) =x² +5
suppose f (x) = y then
y = x² +5
x ² = y-5
[tex]\displaystyle x=\sqrt{y-5}\\\\f^{-1}(y)=\sqrt{y-5}\\\\f^{-1}(x)=\sqrt{x-5}[/tex]
Learn more
the inverse of the function f(x) =2x-10
https://brainly.com/question/628130
Keywords : function, invers
#LearnWithBrainly
Answer:
[tex]f^{-1}(x)=(+/-)\sqrt{x-5}[/tex]
Step-by-step explanation:
we have the function
[tex]f(x)=x^{2} +5[/tex]
Let
[tex]y=f(x)[/tex]
[tex]y=x^{2} +5[/tex]
step 1
Exchange the variables, x for y and y for x
[tex]x=y^{2} +5[/tex]
step 2
Isolate the variable y
Subtract 5 both sides
[tex]x-5=y^{2}[/tex]
step 3
Take square root both sides
[tex]y=(+/-)\sqrt{x-5}[/tex]
step 4
Find the inverse
[tex]f^{-1}(x)=y[/tex]
so
[tex]f^{-1}(x)=(+/-)\sqrt{x-5}[/tex]